2013
DOI: 10.1063/1.4795825
|View full text |Cite|
|
Sign up to set email alerts
|

Semilocal and hybrid density embedding calculations of ground-state charge-transfer complexes

Abstract: We apply the frozen density embedding method, using a full relaxation of embedded densities through a freeze-and-thaw procedure, to study the electronic structure of several benchmark ground-state charge-transfer complexes, in order to assess the merits and limitations of the approach for this class of systems. The calculations are performed using both semilocal and hybrid exchange-correlation (XC) functionals. The results show that embedding calculations using semilocal XC functionals yield rather large devia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 102 publications
1
22
0
Order By: Relevance
“…It was shown that choosing single molecular systems as subsystems in subsystem DFT simulations provides the most beneficial error cancelation between the nonadditive kinetic energy and the nonadditive exchange–correlation functionals employed. The error cancelation is particularly important in the computation of radical species, that is, where semilocal exchange–correlation functionals exhibit the largest deviation from reality due to the self‐interaction error …”
Section: Computational Detailsmentioning
confidence: 99%
“…It was shown that choosing single molecular systems as subsystems in subsystem DFT simulations provides the most beneficial error cancelation between the nonadditive kinetic energy and the nonadditive exchange–correlation functionals employed. The error cancelation is particularly important in the computation of radical species, that is, where semilocal exchange–correlation functionals exhibit the largest deviation from reality due to the self‐interaction error …”
Section: Computational Detailsmentioning
confidence: 99%
“…In fact, for dipole-dipole and hydrogen bond complexes the TPSS/TPSS-L method is the most accurate, closely followed by the PBE/PBE approach, whereas the PBE0/PBE is not so accurate for these systems [21,22]. On the other hand, PBE0/PBE is very accurate for weakly-interacting and charge-transfer systems [24].…”
Section: Resultsmentioning
confidence: 97%
“…This is due to its promise of achieving potentially exact results at a reduced computational cost, as well as to the high insight into the nature of interacting systems provided by the associated embedding potentials. Thus, numerous applications related to non-covalent [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] as well as covalent bonded systems [28][29][30][31] have been considered. In addition, the frozen density embedding (FDE) method [3,32,33] has emerged as a practical tool for efficient simulations of different properties [18,[33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown [125][126][127] that employing hybrid XC functionals (i.e. functionals including a fraction of the HF exact exchange) for the evaluation of the intra-fragment XC energy, greatly improves the quality of FDE for chargetransfer complexes, w.r.t.…”
Section: Note On Self-interactionmentioning
confidence: 99%